Advanced Psychology - Turner Lynda (Hodder & Stoughton, 2003)
This book provides students and teachers of AQA(B) level psychology with a comprehensive accessible learning-oriented textbook.How to Use this Book, Acknowledgements, Definition and Classification of atypical behaviour, Anxiety and Eating Disorders, Mood Disorders and Schizophrenia, Treatment of atypical Behaviour, Glossary, Bibliography, Index.